FAMILY CONFLICT REFLECTED IN KEVIN KWAN’S “RICH PEOPLE PROBLEM”; A SOCIOLOGICAL APPROACH - Indah Purnama; Ayu Melati Ningsih (Fakultas Sastra UMN AL Washliyah, 2021)
The objective of the research was to analyze the family conflict that was reflected in the novel Rich People Promblem. This research used a sociological approach and social action theory. This research used a qualitative research. This research was taken from the novel